Engineering Transcriptional Regulation to Control Pdu Microcompartment Formation - Kim, Edward Y.; Jakobson, Christopher M.; Tullman-Ercek, Danielle (PloS one, 2014)
Bacterial microcompartments (MCPs) show great promise for the organization of engineered metabolic pathways within the bacterial cytoplasm. This subcellular organelle is composed of a protein shell of 100-200 nm diameter that natively encapsulates multi-enzyme pathways. The high energy cost of synthesizing the thousands of protein subunits required for each MCP demands precise regulation of MCP formation for both native and engineered systems. Here, we study the regulation of the propanediol utilization (Pdu) MCP, for which growth on 1,2-propanediol induces expression of the Pdu operon for the catabolism of 1,2-propanediol. We construct a fluorescence-based transcriptional reporter to investigate the activation of the Ppdu promoter, which drives the transcription of 21 pdu genes. Guided by this reporter, we find that MCPs can be expressed in strains grown in rich media, provided that glucose is not present. We also characterize the response of the Ppdu promoter to a transcriptional activator of the pdu operon, PocR, and find PocR to be a necessary component of Pdu MCP formation. Furthermore, we find that MCPs form normally upon the heterologous expression of PocR even in the absence of the natural inducer 1,2-propanediol and in the presence of glucose, and that Pdu MCPs formed in response to heterologous PocR expression can metabolize 1,2-propanediol in vivo. We anticipate that this technique of overexpressing a key transcription factor may be used to study and engineer the formation, size, and/or number of MCPs for the Pdu and related MCP systems.